2018
DOI: 10.35808/ijeba/175
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work Stress, Working Cost, Compensation and Work Discipline on Employee’ Productivity

Abstract: This study aims to identify the effect of work stress, workload, compensation and work discipline on work productivity of employees of PT., Tokio Marine Life Insurance Indonesia. The research was conducted quantitatively by a descriptive associative method. Data collection was done by survey using questionnaire. The population of this research is employees of PT., Tokio Marine, as many as 259 employees. The study population was used as the source of the sample, and the sample obtained amounted to 120 responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Meaning that the better the motivation, and compensation will affect work results which will result in good productivity (Ekhsan et al, 2019;Bawoleh et al, 2015). Second hypothesis: Compensation (X2) has an effect on productivity (Y) (Pawirosumarto and Iriani, 2018;Fajarto et al, 2019). The result of the P-Value is 0.000 ≤ 0.05, so it can be concluded that there is an effect of work compensation on employee work productivity at PT.…”
Section: Resultsmentioning
confidence: 99%
“…Meaning that the better the motivation, and compensation will affect work results which will result in good productivity (Ekhsan et al, 2019;Bawoleh et al, 2015). Second hypothesis: Compensation (X2) has an effect on productivity (Y) (Pawirosumarto and Iriani, 2018;Fajarto et al, 2019). The result of the P-Value is 0.000 ≤ 0.05, so it can be concluded that there is an effect of work compensation on employee work productivity at PT.…”
Section: Resultsmentioning
confidence: 99%
“…Research by Dotulong & Assagaf (2015) stated that work discipline as an independent variable partially doesn't influence work productivity (variable dependent). Same as research by Pawirosumarto & Iriani (2018) indicates that work discipline (X1) has no effect partially on work productivity with a p-value of 0.923. For some research, many of them stated that work discipline and motivation significantly impact work productivity.…”
Section: Introductionmentioning
confidence: 86%
“…Indicators of compensation are : 1) salary, 2) Incentive, 3) Bonus, 4) Benefits, 5) Facilities (Badriyah, 2015). Previous studies about Compensation among researchers: (Satmoko, 2018), (Novianto and Sujana, 2015), (Tanri, 2018), (Dewi, 2021), (Karsono et al, 2019), (Putra and Mujiati, 2022), (Pawirosumarto and Iriani, 2018), (Trang, 2016).…”
Section: Compensationmentioning
confidence: 99%